2016
DOI: 10.3389/fphys.2016.00134
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptors of Human Neural Cells Play Crucial Roles in Alzheimer's Disease

Abstract: In aged subjects, late-onset Alzheimer's disease (LOAD) starts in the lateral entorhinal allocortex where a failure of clearance mechanisms triggers an accumulation of neurotoxic amyloid-β42 oligomers (Aβ42-os). In neurons and astrocytes, Aβ42-os enhance the transcription of Aβ precursor protein (APP) and β-secretase/BACE1 genes. Thus, by acting together with γ-secretase, the surpluses of APP and BACE1 amplify the endogenous production of Aβ42-os which pile up, damage mitochondria, and are oversecreted. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 247 publications
(366 reference statements)
5
66
0
Order By: Relevance
“…The primary goal of the current study was to unmask the molecular players that contribute to the dysregulation of astrocyte physiology during AD progression. It is well known in these cells that Aβ promotes calcium imbalance by mechanisms that involve endoplasmic reticulum activation and stress (Alberdi et al ., ), regulation of L‐type calcium channel expression (Daschil et al ., ), and calcium‐sensing receptor activation (Chiarini et al ., ). In addition to these activities, the glial cellular stress generated via NOX enzyme activities may contribute to leading glia‐mediated neurotoxicity in AD (Angelova & Abramov, ).…”
Section: Discussionmentioning
confidence: 97%
“…The primary goal of the current study was to unmask the molecular players that contribute to the dysregulation of astrocyte physiology during AD progression. It is well known in these cells that Aβ promotes calcium imbalance by mechanisms that involve endoplasmic reticulum activation and stress (Alberdi et al ., ), regulation of L‐type calcium channel expression (Daschil et al ., ), and calcium‐sensing receptor activation (Chiarini et al ., ). In addition to these activities, the glial cellular stress generated via NOX enzyme activities may contribute to leading glia‐mediated neurotoxicity in AD (Angelova & Abramov, ).…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, reports indicated the calcium sensing receptor (CaSR) as a potential key player in AD [24][25][26]. CaSR is a G-protein coupled receptor (GPCR) mainly expressed in the parathyroid glands where it exerts its primary role in sensing extracellular Ca 2+ levels and in regulating parathyroid hormone secretion accordingly [27].…”
Section: Introductionmentioning
confidence: 99%
“…The PDGF-mediated activation of STAT1/3 has been demonstrated to up-regulate the gene expression of c-Jun and AP1 transcription activators, which are involved in PASMC growth. On the other hand, previous studies reported that CaSR expression is regulated by STAT1/3 in addition to proinflammatory cytokines such as IL-1b and IL-6 (19,24). STAT1/3 modulate the P1 activity of CaSR via the STAT element in exon 1A (19).…”
Section: Discussionmentioning
confidence: 94%